Contrasting the amygdala activity and functional connectivity profile between antidepressant-free participants with major depressive disorder and healthy controls: A systematic review of comparative fMRI studies. (September 2022) - Tassone, Vanessa K.; Demchenko, Ilya; Salvo, Joseph; Mahmood, Raesham; Di Passa, Anne-Marie; Kuburi, Sarah; Rueda, Alice; Bhat, Venkat
Highlights: Neuroimaging results concerning the amygdala functioning in MDD are variable. We reviewed amygdala functional imaging results in antidepressant-free MDD. Among MDD participants, amygdala was hyperactive in response to negative stimuli. MDD FC alteration between amygdala, PFC, ACC, insula, temporal, and parietal cortex. Decreased connectivity between amygdala and OFC, striatum, and cerebellum in MDD. Abstract: Functional neuroimaging research suggests that the amygdala is implicated in the pathophysiology of major depressive disorder (MDD). This systematic review aimed to identify consistently reported amygdala activity and functional connectivity (FC) abnormalities in antidepressant-free participants with MDD as compared to healthy controls at baseline (i.e., before treatment initiation or experimental manipulation). A search for relevant published studies and registered clinical trials was conducted through OVID (MEDLINE, PsycINFO, and Embase) and ClinicalTrials.gov with an end date of March 7th, 2022. Fifty published studies and two registered clinical trials were included in this review. Participants with MDD frequently exhibited amygdala hyperactivity in response to negative stimuli, abnormal event-related amygdala-anterior cingulate cortex (ACC) FC, and abnormal resting-state amygdala FC with the insula and the prefrontal, temporal, and parietal cortices. Decreased resting-state FC was consistently found between the amygdala and the orbitofrontal cortex, striatum, cerebellum, and middle/inferior frontal gyri. Due to the limited number of studies examining resting-state amygdala activity and FC with specific subregions of interest, including those within the ACC, further investigation is warranted.